Analysis of Eutrophication Potential in Main Drinking Water Basins of Istanbul - Karpuzcu, Mahmut Ekrem; Fakioglu, Malhun; Ozturk, Izzet (Wiley, 2021)
AbstractEutrophication potential in three main drinking water reservoirs of Istanbul is investigated. The eutrophication analysis is conducted by a phosphorus mass balance model using the point and nonpoint sources of pollution with the data provided by the Istanbul Water and Sewerage Administration. In addition to the mass balance model, the reservoirs are also evaluated based on trophic state index calculations. The results indicate that Istanbul's main drinking water reservoirs are either under eutrophication danger or already under eutrophic conditions. While reduction of nonpoint source loads using a series of best management practices is recommended for Omerli and Buyukcekmece Reservoirs, additional measures to mitigate internal eutrophication is necessary for Terkos Reservoir. Results of this study provide insight into management and control scenarios to prevent impacts of eutrophication in these reservoirs.